Encapsulated Cell Technology-Based Delivery of a Complement Inhibitor Reduces Choroidal Neovascularization in a Mouse Model - Annamalai, Balasubramaniam (Transl Vis Sci Technol, 2018)
PURPOSE: Age-related macular degeneration (AMD) is a slowly progressing disease, and risk appears to be tied to an overactive complement system. We have previously demonstrated that mouse choroidal neovascularization (CNV) and smoke-induced ocular pathology can be reduced with an alternative pathway (AP) inhibitor fusion protein consisting of a complement receptor-2 fragment linked to the inhibitory domain of factor H (CR2-fH) when delivered systemically. Here we developed an experimental approach with genetically engineered encapsulated ARPE-19 cells to produce CR2-fH intravitreally. METHODS: ARPE-19 cells were generated to stably express CR2 or CR2-fH, microencapsulated using sodium alginate, and injected intravitreally into 2-month-old C57BL/6J mice. CNV was induced using argon laser photocoagulation 4 weeks postinjection. Presence of capsules and progression of CNV was analyzed using optical coherence tomography. Bioavailability of CR2-fH was evaluated in retina sections by immunohistochemistry, and efficacy as an AP inhibitor by C3a ELISA. RESULTS: Secretion of CR2-fH or CR2 from encapsulated ARPE-19 cells was confirmed. An efficacious concentration of CR2-fH capsules to reduce CNV was identified. Bioavailability studies showed that CR2-fH was present in capsules and retinas of injected mice, and reduced CNV-associated ocular C3a production. CONCLUSIONS: These findings indicate that the AP inhibitor CR2-fH, when generated intravitreally, can reduce CNV in mouse. TRANSLATIONAL RELEVANCE: Encapsulated ARPE-19 cells secreting CR2-fH or perhaps other antiangiogenic or prosurvival factors might be useful as a potential therapeutic tool to treat age-related macular degeneration.